Cytoprotective Effect of Short-Term Pretreatment with Proanthocyanidin on Human Gingival Fibroblasts Exposed to Harsh Environmental Conditions - Kurauchi, Michiko (PLoS One, 2014)
Our previous study showed that exposing mouse fibroblasts to proanthocyanidin (PA) for only 1 min accelerated cell proliferation in a concentration-dependent manner. In this study, exposing human gingival fibroblasts (HGFs) to PA for 1 min similarly accelerated the proliferative response of the cells. Besides the accelerated proliferative response, PA showed a cytoprotective effect on HGFs exposed to harsh environmental conditions; short-term exposure of HGFs in the mitotic phase to pure water or physiological saline resulted in a lower recovery of viable cells. Pretreatment and concomitant treatment with PA improved the low recovery of cells exposed to pure water or physiological saline. In addition, HGFs exposed to PA for 1 min proliferated well even after being cultured in serum-free medium. In 100% confluent HGFs, being cultured in serum-free medium resulted in a high intracellular reactive oxygen species (ROS) level, but pretreatment with PA prevented the cells from increasing intracellular ROS. Thus, the results suggest that a short-term PA treatment exerts cytoprotective effects on HGFs exposed to harsh environmental conditions by improving the intracellular oxidative stress response.